Learning To Lead From The Urban Grassroots: Self-Transformation And Sustainable Leadership In The Urban Village Office - Fransiska Grassela Sucipto (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to analyze the influence of self-transformation on sustainable leadership among government officials working in urban village offices, focusing on how individual learning and self-development contribute to creating adaptive, collaborative, and sustainability-oriented leadership styles. The research stems from the challenges faced by local government officials in responding to increasingly complex public service demands amid dynamic social and bureaucratic changes. A quantitative approach was employed, utilizing a survey method, with questionnaires distributed to 150 employees across various urban villages in Jember Regency. The research instruments were developed based on self-transformation indicators, including self-awareness, continuous learning, adaptability, and intrinsic motivation, as well as sustainable leadership indicators encompassing collaboration, ethical responsibility, organizational learning, and social sustainability orientation. Data were analyzed using simple linear regression to test the direct relationship between the two variables. The results indicate that self-transformation has a positive and significant effect on sustainable leadership among urban village officials. This means that the higher an individual’s level of self-awareness and ability to develop themselves, the stronger their tendency to implement sustainability-oriented leadership practices. The study concludes that strengthening self-transformation through training, work reflection, and collaborative learning can serve as a key strategy in building sustainable public leadership at the local level. These findings are expected to provide a foundation for local governments in designing capacity development programs aligned with the principles of sustainable governance.